White Guys: Studies in Post-Modern Domination and Difference - Dunk, Thomas (Labour / Le Travail, 1997)
The article reviews the book, "White Guys: Studies in Post-Modern Domination and Difference," by Fred Pfeil.
Keywords: BLACK white differences; BOOKS -- Reviews; Nonfiction; PFEIL, Fred; WHITE Guys: Studies in Post-Modern Domination & Difference (Book)